2014
DOI: 10.1002/jbm.a.35292
|View full text |Cite
|
Sign up to set email alerts
|

Construction of three-dimensional liver tissue models by cell accumulation technique and maintaining their metabolic functions for long-term culture without medium change

Abstract: Three-dimensional (3D) hepatocyte cultures have attracted much attention to obtain high biological functions of hepatocyte for pharmaceutical drug assessment. However, maintaining the high functions for over one month is still a key challenge although many approaches have been reported. In this study, we demonstrate for the first time simple and rapid construction of 3D-hepatocyte constructs by our cell accumulation technique and their high biological functions for one month, without any medium change. The hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 50 publications
(101 reference statements)
2
11
0
1
Order By: Relevance
“…In fact, it has been shown that simply transitioning from 2D to 3D resulted in increased HEPG2 albumin expression and secretion [28]. This is not limited to HEPG2s either.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it has been shown that simply transitioning from 2D to 3D resulted in increased HEPG2 albumin expression and secretion [28]. This is not limited to HEPG2s either.…”
Section: Resultsmentioning
confidence: 99%
“…Although typically used in surface engineering applications, or to tune membrane's permeability, LbL methodologies are being used in liver TE. Despite the number studies using LbL are scarce, LbL deposition of fibronectin and gelatin on the surface of HepG2 cells renders a multilayered adhesive film that is fundamental for further cell accumulation . Surprisingly, the cell constructs obtained by this method were able to sustain cell viability up to 27 d of culture, with high albumin and cytochrome P450 enzyme expressions ( Figure ).…”
Section: Conventional Versus Advanced Processing Technologies For LIVmentioning
confidence: 99%
“…Adapted with permission. [218] Copyright 2014, John Wiley and Sons. PDMS Decellularized liver matrix + GelMA HepG2 cells [234][235][236] PEG hiPSCs [232,237] Liver organoids Matrigel Primary hepatocytes [238] Alginate Decellularized liver matrix + GelMA HepG2 cells [229,230] PEG PDMS + PEG hiPSCs [232,237,239] www.advancedsciencenews.com www.advhealthmat.de…”
Section: Wwwadvancedsciencenewscom Wwwadvhealthmatdementioning
confidence: 99%
“…If different scaffolds are grown in separate bioreactors, they each develop a cell population with distinct characteristics. These scaffolds can be bound together in vitro or in vivo using a variety of layering techniques, usually crosslinking (Gleghorn, Lee, Cabodi, Stroock, & Bonassar, ; Gurkan et al, ; Harley et al, ; B. S. Soo Kim et al, ; M. Kim & Kim, ; Levingstone et al, ; Pi et al, ; G. Yang, Lin, Rothrauff, Yu, & Tuan, ), sintering (Camarero‐Espinosa, Rothen‐Rutishauser, Weder, & Foster, ; Costa et al, ; Mosher, Spalazzi, & Lu, ; Spalazzi, Doty, Moffat, Levine, & Lu, ), or by inducing extracellular matrix (ECM) deposition (Asano, Shimoda, Okano, Matsusaki, & Akashi, ; Matsusaki et al, ; Matsuzawa, Matsusaki, & Akashi, ; Ng, Qi, Yeong, & Naing, ; Nishiguchi, Yoshida, Matsusaki, & Akashi, ; Papenburg et al, ), but it is difficult to predict the interface that will form (Figure b‐i). In the DCB, two parallel flow inlets connect to a common chamber, followed by two flow outlets (Figure b‐ii).…”
Section: Introductionmentioning
confidence: 99%